PENGARUH STRUKTUR KEPEMILIKAN SAHAM PERUSAHAAN TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) - Purwinda Lestari (2017)
This study was conducted to examine the effect of the ownership structure of the company's stock on Corporate Social Responsibility Disclosure. This study uses the manufacturing companies listed in Indonesia Stock Exchange as a sample. Sampling technique using purposive sampling (purposive sampling method). Selection of a sample of 148 manufacturing companies listed in Indonesia Stock Exchange in 20132015 resulted in 28 companies that are acceptable. Testing the hypothesis in this study using Multiple Linear Regression Analysis with SPSS 21 and a significance level of 5 %. The results of the testing showed that: (1) instutisonal ownership has no a significant influence on the corporate social responsibility disclosure because it has a significance level of 0.355 is greater than the specified level α = 0.05. (2) manajerial ownership has no significant effect on the capital structure because it has a significance level of 0.588 is greater than the specified level α = 0.05.(3) foreign ownership has no a significant influence on the corporate social responsibility disclosure because it has a significance level of 0.355 is greater than the specified level α = 0.05 (4) public ownership has no a significant influence on the corporate social responsibility disclosure because it has a significance level of 0.454 is greater than the specified level α = 0.05.